An Analytical Study of Thyroid Nodules by Ultrasonography findings - Dr. Hulesh Mandle (Innovative Journal of Medical and Health Sciences, 2011)
Introduction: Thyroid nodules are common, their prevalence being chiefly dependent on the identification technique. The estimated prevalence by palpation alone ranges from 4% to 7%, up to 67% by ultrasound, and fifty percent at autopsy with a noticeably higher incidence in iodine deficient provinces.This study was aimed to determine the ultrasound imaging findings of thyroid nodules in patients and correlate it with clinical records to develop a standardized diagnosis system for interpreting thyroid ultrasound imaging. Methods: This Retrospective Analytical study involveddata of 200 of the randomly selected patients ( candidates / study subjects ) who seek care for Thyroid Nodules between Aug 2009 to Nov 2009 were retrospectively identified.From Lew et al. guidelines ultrasound of nodule margins, suggestive of malignancy guidelines was adopted. A fine needle aspiration (FNA) biopsy was recommended to the referring physician is required.[14,15] All participants provided informed written consent to participate in it.Patients with diagnosed thyroid nodules of more than 1 cm and who underwent ultrasonography were included. Results: From all nodules, 21.50% were single and 78.5% were multiple nodules; 53 nodules (26.5%) were solid and 157 (78.5%) cystic. Concerning echogenicity, 46 nodules (23%) were Hypo-echo , 44 nodules (22%) were Hyper-echo & rest were Iso echoic. 192 nodules (96.0%) had a regular edge. 59 nodules (29.5%) were without Halo. 157 nodules (78.5%) were larger than 15mm. According to histopathology results, the benign nodules were 92% and malignant cases were 08% Conclusion:Based on the result of this study, thyroid nodule size must not be considered as a criterion for malignancy and thyroid nodules of any size must be suspected as malignant. Important criteria for malignancy include irregular edges, being Solid hypoechogenicity and being a single nodule respectively. However, the presence of calcifications in the nodule by US indicates a higher risk of malignancy and should prompt the clinician to evaluate the nodule further with repeat FNA.